Alternative bi-Hamiltonian structures for WDVV equations of associativity - Kalayci, J.; Nutku, Y. (IOP Publishing, 1998)
The WDVV equations of associativity in 2-d topological field theory are completely integrable third order Monge-Ampre equations which admit bi-Hamiltonian structure. The time variable plays a distinguished role in the discussion of Hamiltonian structure whereas in the theory of WDVV equations none of the independent variables merits such a distinction. WDVV equations admit very different alternative Hamiltonian structures under different possible choices of the time variable but all these various Hamiltonian formulations can be brought together in the framework of the covariant theory of symplectic structure. They can be identified as different components of the covariant Witten-Zuckerman symplectic 2-form current density where a variational formulation of the WDVV equation that leads to the Hamiltonian operator through the Dirac bracket is available.
Keywords: High Energy Physics - Theory; WDVV-equations; High Energy Physics - Theory (hep-th); Gromov-Witten invariants, quantum cohomology, Frobenius manifolds; FOS: Physical sciences; Topological quantum field theories (aspects of differential topology); bi-Hamiltonian structure